A New Educational Model for Online Flourishing: A Pragmatic Approach to Integrating Moral Theory for Cyber-flourishing. (3rd April 2022) - Harrison, Tom
ABSTRACT: Online risks and harms, including cyber-bullying, trolling, revenge porn and digital harassment, are an everyday reality in many young people's lives. Educators are increasingly being called upon to address these concerns but are not adequately equipped to do so. In this article the case is made for a new educational model for cyber-flourishing. The model is constructed through a pragmatic approach to moral theory, adopting the central tenets of deontology, utilitarianism and virtue ethics, and showing how these can be integrated and put to work by teachers to tackle online harms. The model is comprised of three core components, cyber-rules, cyber-wisdom and cyber-flourishing, and each is explained in detail in the article. Cyber-rules must be put in place by schools to provide the foundations for the cultivation of character and cyber-wisdom. Cyber-wisdom is the individual quality of doing the right thing, at the right time, especially when no one is looking. Cyber-flourishing is defined as authentic happiness that comes from living morally in the online world, and is the utility value that we should all strive for. The article concludes by outlining nine educational practices that demonstrate how teachers can adopt and implement the model in their schools. The model is the first attempt in the world to integrate moral theory into an educational model that provides an overarching and whole-school approach to tackling pressing everyday online concerns.